Seafarer Readiness for Green Shipping Transition - Insights from Maritime Education and Industry Professionals - Panderaja Soritua Sijabat; Tri Cahyadi; Winarno Winarno; Riyanto Riyanto; Larsen Barasa; Cris Kuntadi; Marudut Bernadtua Simanjuntak (Institut Nalanda, 2025)
The transition to green shipping is a critical challenge for the maritime sector, requiring a shift in both technological adoption and workforce preparedness. This research examines the readiness of seafarers for this transition, focusing on the alignment between maritime vocational education and industry needs. The analysis addresses the gap between theoretical knowledge and practical application in green shipping technologies. The research aims to answer key questions regarding the integration of sustainability into maritime education, seafarer readiness, and the alignment of training with industry requirements. A qualitative methodology combining Systematic Literature Review (SLR) and interviews with 10 maritime professionals, educators, and graduates was used to gather insights. The SLR provided a theoretical framework for understanding the green shipping transition, while the interviews revealed practical barriers to implementing sustainable practices in training programs. The findings show a clear misalignment between current educational practices and industry demands, with a need for hands-on training and stronger collaboration between academia and industry. The research emphasizes the importance of integrating green shipping technologies into curricula and fostering a culture of sustainability in the maritime sector. This study contributes valuable insights into the preparation of seafarers for a sustainable future in the maritime industry, offering practical recommendations for improving education and industry collaboration.